2018
DOI: 10.3766/jaaa.16148
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Hearing Aid Adoption and Use: A Qualitative Study

Abstract: Similar themes emerged from qualitative analysis across groups of people with hearing loss. More information for those with hearing loss and those with hearing aids and scheduled follow-up appointments for those with hearing aids are essential to improve hearing aid adoption and use in older people. Further research should focus on the most suitable methods of distributing this information and how often follow-up appointments should take place to achieve optimal hearing aid adoption and use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
44
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 44 publications
2
44
0
6
Order By: Relevance
“…Hearing aid success is often defined as consistent and proper use of hearing aids [Fischer et al, 2011;Chien and Lin, 2012;McCormack and Fortnum, 2013;Gallagher and Woodside, 2018]. Given the link between patientperceived benefit and hearing aid acquisition and use, PROMs may help guide patients toward successful hearing rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hearing aid success is often defined as consistent and proper use of hearing aids [Fischer et al, 2011;Chien and Lin, 2012;McCormack and Fortnum, 2013;Gallagher and Woodside, 2018]. Given the link between patientperceived benefit and hearing aid acquisition and use, PROMs may help guide patients toward successful hearing rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…PROMs may also help providers direct changes in hearing aid use to maximize perceived benefit and examine non-audiologic factors that are commonly cited as leading to increased success with hearing aids. These include increased family support, access to counselling, hearing aid comfort, ease of hearing aid use, and a favorable cost-benefit ratio of the hearing aid device [McCormack and Fortnum, 2013;Gallagher and Woodside, 2018]. These factors are more difficult to predict using audiologic measures of hearing aid benefit alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Raising awareness of hearing problems by implementing feasible screening methods should lead to a higher number of older adults receiving proper hearing rehabilitation. This is especially important in people with severe hearing loss (i.e., a PTA ≥ 60 dB) who are more likely to adopt the use of a hearing aid and have reported a higher QOL due to hearing rehabilitation [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…This is especially important in people with severe hearing loss (i.e., a PTA ≥ 60 dB) who are more likely to adopt the use of a hearing aid and have reported a higher QOL due to hearing rehabilitation. (45)(46)(47) Ensuring that validated questionnaires are adopted and applied across different cultural contexts while retaining the reliability and validity of the original version is a challenge. For our study, we found that the reliability was very good for our Thai version and that our internal consistency was higher than that achieved by Swedish version and comparable to that of the original version.…”
Section: Discussionmentioning
confidence: 99%